2023
DOI: 10.1002/ejhf.2822
|View full text |Cite
|
Sign up to set email alerts
|

Safety and performance of a novel implantable sensor in the inferior vena cava under acute and chronic intravascular volume modulation

Abstract: Aims The management of congestion is one of the key treatment targets in heart failure. Assessing congestion is, however, difficult. The purpose of this study was to investigate the safety and dynamic response of a novel, passive, inferior vena cava (IVC) sensor in a chronic ovine model. Methods and results A total of 20 sheep divided into three groups were studied in acute and chronic in vivo settings. Group I and Group II included 14 sheep in total with 12 sheep receiving the sensor and two sheep receiving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Chronic integration of the sensors showed a thin, re-endothelialized neointima with maintained sensitivity to infused volume. Normalized IVC area significantly changed from 25 ± 17% to 43 ± 11% ( p = 0.007) with 300 mL infused, whereas RAP required 1200 mL of infused volume before a statistically significant change from 3.1 ± 2.6 mmHg to 7.5 ± 2.0 mm Hg ( p = 0.02) [ 73 ].…”
Section: Sensor-based Hf Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic integration of the sensors showed a thin, re-endothelialized neointima with maintained sensitivity to infused volume. Normalized IVC area significantly changed from 25 ± 17% to 43 ± 11% ( p = 0.007) with 300 mL infused, whereas RAP required 1200 mL of infused volume before a statistically significant change from 3.1 ± 2.6 mmHg to 7.5 ± 2.0 mm Hg ( p = 0.02) [ 73 ].…”
Section: Sensor-based Hf Monitoringmentioning
confidence: 99%
“…This could have important clinical implications by allowing earlier detection of hypervolemia compared with pressure sensors, leading to prompt clinical intervention and positively affecting the outcomes of HF patients. Additionally, implanting the sensor in the IVC and its integration through endothelialization has shown no negative effect on long-term sensor performance in response to fluid accumulation [ 73 ]. Nevertheless, there are certain limitations to consider in both animal studies, including experiments with healthy sheep, the possibility of potential side effects in relation to the duration of experiments conducted on the same day, and ambiguity concerning the application of experimental findings to humans, especially with HF.…”
Section: Sensor-based Hf Monitoringmentioning
confidence: 99%
“…A novel device, a passive, inferior vena cava sensor was tested in a chronic ovine model. The inferior vena cava area was accurately remotely measured, providing a higher sensitivity than filling pressures 42 …”
Section: Devicesmentioning
confidence: 99%
“…The inferior vena cava area was accurately remotely measured, providing a higher sensitivity than filling pressures. 42…”
Section: Devicesmentioning
confidence: 99%
“…In this issue of the Journal, Sheridan and colleagues report an early pre-clinical study on a total of 20 sheep evaluating the safety and performance of the novel percutaneous, wireless, passive, radiofrequency-based, implantable FIRE1 System (Foundry Innovation & Research 1 Ltd., Dublin, Ireland), allowing real-time chronic remote monitoring of IVC CSA. 7 The device requires a transvenous insertion and deployment in the IVC and is coupled with an extracorporeal sensor incorporated in a belt. The authors found no peri-procedural complications and a good endothelialization of the device struts up to 180 days after implant.…”
mentioning
confidence: 99%